Building Agents with OpenAI Agents SDK : Create Practical AI Agents and Agentic Systems Through Hands-On Projects. - Habib, Henry. (Packt Publishing, Limited, 2025)
Master OpenAI's Agents SDK to design production-ready AI agents and agentic systems that solve real-world problems with practical guidanceGet your book with a free PDF, AI Assistant, and Next-Gen Reader Key Features Gain a complete understanding of the OpenAI Agents SDK features including models, tools, memory, guardrails, orchestration, tracing.